Response of Peanut (Arachis Hypogaea L.) to Nitrogen, Minor Elements and Phosphorus Fertilization on a Newly Terraced Ultisol in Jamaica - Campbell, Vincent A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
52 páginas